Superior mechanical properties for an additively manufactured crack-free Ni-based superalloy with an inherited metastable microstructure after heat treatment - Dongyu Wei; Lu Shi; Wenzhe Zhou; Yusheng Tian; Beiya Wang; Rui Wang; Jian He; Decheng Kong; Guoliang Zhu; Baode Sun (Journal of Materials Research and Technology)
Localized non-equilibrium and rapid solidification usually generate a distinctive metastable microstructure in metals and alloys produced through the laser powder bed fusion. Therefore, it is crucial to modulate the printed microstructure for the final mechanical properties. Several heat treatment procedures were developed to control the cellular structure and carbides of the LPBF (Laser powder bed fusion) ZGH4142 alloy in this work. The relationship between heat treatment, microstructure, and mechanical properties was thoroughly investigated. It shows that traditional standard heat treatment is not the optimal approach for ZGH4142 alloy, and the specimens exhibit moderate high-temperature strength but reduced ductility after high-temperature heat treatment, owing to the presence of oversized carbides. However, directly aged ZGH4142 alloy (900 °C) demonstrates a superior combination of high-temperature ultimate tensile strength (139.7 MPa) and elongation (11.5 %) at 1100 °C. The preserved metastable cellular microstructures hinder dislocation transfer between adjacent cells and limit dislocation slipping within cells for the directly aged counterparts, and the fine carbides strengthen the grain boundary and prevent premature instability therein. The research findings provide valuable insights for exploring heat treatment processes to maintain the inherited metastable microstructure formed during the printing process for other AM Ni-based superalloys.